In vitro antiurolithiatic activity of c-phycocyanin isolated from Spirulina platensis - Subhashini, Dr. N. J. P. (Asian Journal of Pharmaceutics (AJP), 2021)
Background: Pashanabheda is used as antiurolithiatic in Ayurveda. In the present study, Spirulina platensis was selected for isolation of its active constituent, C-Phycocyanin (C-PC), and screening for in vitro antiurolithiatic potentials. Objective: Screening of compound isolated from S. platensis for antiurolithiatic potentials. Materials and Methods: The algae sample was subjected to preliminary analysis. Then, the sample was processed for the extraction of phycocyanin from S. platensis by various extraction methods, purified and then characterization was performed by reverse phase high-pressure liquid chromatography and by mass spectrometry. Finally, in vitro antiurolithiatic activity was screened by nucleation and aggregation assay. Results: The isolated C-PC exhibited inhibitory action in both nucleation and aggregation assays to significant level. In the aggregation assay gradually decrease in the calcium oxalate (CaOx) crystal nucleation as well as growth was observed by light microscopy. The findings of the nucleation assay indicate that phytoconstituents inhibited the crystallization of CaOx in solution. There were less and smaller particles with increasing concentration of the phycocyanin. The increasing concentrations of C-PC (100, 200, 300, 400, and 500 Î¼g/ml) inhibited the CaOx crystal growth. C-PC demonstrated slightly better results compared to cystone standard solution to inhibit the formation of CaOx dihydrate crystals in the nucleation assay. Conclusion: The isolated C-PC has shown antiurolithiatic effect by significantly reducing the size and growth of calculi in the kidneys in the in vitro assays